Comparative study on the calculation methods of ecological base flow in a mountainous river - Gao, Cheng; Hao, Manqiu; Song, Lianghong; Rong, Wang; Shao, Shuaibing; Huang, Ying; Guo, Yufa; Liu, Xueyao (Frontiers in Environmental Science, 2022)
As the social economy is further developed, there have been increasingly severe ecological and environmental issues. For instance, rivers located in mountainous areas are often encountered with the issue of zero flow. The ecological base flow was put forward to ensure the continuous flow of rivers, to realize the minimum ecological function, and to meet the most fundamental requirements of sustaining the river ecosystem. Wulong River Basin in Yantai City of China was taken as example here. Based on the runoff data collected in the Tuanwang Hydrological Station from 1960 to 2016, the measured runoff data was restored to natural runoff sequence by adopting the item-by-item investigation method. The different ecological base flows of Wulong River were calculated by adopting the Tennant Method, the Qp90 Method, the Texas Method, the Base Flow Ratio Method, the Tessman Method, and Wetted Perimeter Method. The research findings have shown that the Base Flow Ratio Method proves to be the optimal approach for calculating the ecological base flow of Wulong River. Based on the analysis of the assurance degree of ecological base flow, the period from April to June is the period with the lowest assurance degree of ecological base flow.